Zeiten der Wachsamkeit - Brendecke, Arndt; Reichlin, Susanne (Vigilanzkulturen / Cultures of Vigilance, 2022)
Just as human attention is subject to considerable fluctuations, vigilance is also temporally unstable. Cultural instructions to be vigilant therefore generally work with temporal structures and natural temporal sequences (such as day and night, light and dark), which they form culturally and make useful. This volume examines this temporal shaping of vigilance by looking at specific historical constellations.